Root functioning, tree water use and hydraulic redistribution in Quercus suber trees: A modeling approach based on root sap flow - David, Teresa S.; Pinto, Clara A.; Nadezhdina, Nadezhda; Kurz-Besson, Cathy; Henriques, Manuel O.; Quilhó, Teresa; Čermák, Jan; Chaves, M. Manuela; Pereira, João S.; David, Jorge S. (Forest Ecology and Management, 2013)
Mediterranean evergreen oaks have to survive a long summer drought. Roots may play a relevant role under these conditions. We studied their structure and function in a mature Quercus suber L. tree in central Portugal. The root system was mapped till the lowest water table level (4.5 m depth). Xylem anatomy was analyzed in a vertical profile belowground. Sap flow was continuously monitored for 1.5 yrs in the stem and roots of this intensively studied tree (heat field deformation method) and in the stem of four trees (Granier method), in relation to environmental variables and predawn leaf water potential. The sources of water uptake were assessed by stable isotope analyses in summer. Results showed a dimorphic root system with a network of superficial roots linked to sinker roots, and a taproot diverting into tangles of deep fine roots submerged for long periods, with parenchyma aerenchyma. Transpiration was not restricted in summer due to root access to groundwater. The isotopic δ18O signature of twig xylem water was similar to that of groundwater in the dry season. Two functional types of superficial roots were identified: shallow connected and deep connected roots. A modeling approach was built considering that each superficial root was linked to a sinker, with part of the root deep connected (between the stem and the sinker) and part shallow connected (between the sinker and topsoil). This conceptual framework simulated tree stem sap flow from root sap flow with a high efficiency (R2 = 0.85) in four plot trees. On an annual basis, soil water and groundwater contributions were 69.5% and 30.5% of stem flow, respectively. Annual hydraulic lift and hydraulic descent were 0.9% and 37.0% of stem flow, respectively. The trees maximize the exploitation of the environmental resources by using the topsoil water during most of the year, and groundwater together with hydraulic lift (nutrient supply) in the dry summer. This study shows that a dimorphic root system, with roots reaching groundwater, is an efficient strategy of Q. suber trees to cope with seasonal drought. Knowledge of the functional behavior of Q. suber trees under shallow water table conditions may contribute to the definition of better adapted management practices and to anticipate their responses to climate change.
Keywords: Drought; groundwater; soil water; Stable isotopes; xylem anatomy

The cellular structure of cork from Quercus cerris var. cerris bark in a materials’ perspective (Industrial Crops and Products, 2011)
Cork in the outer bark of trees is among the valuable raw materials of biological origin due to properties that result mainly from its cellular structure. Large scale commercial utilization of cork has been only achieved with cork from Quercus suber. Another oak species, Quercus cerris, also contains substantial, albeit not continuous, regions of cork that are clearly visible to the naked eye but are so far considered as a waste material. Bark samples of Q. cerris var. cerris trees were collected from the Andırın province, Turkey. Cork portions were separated and their cellular structure was investigated with optical and electron scanning microscopy observations. The results were compared with Q. suber cork. Q. cerris cork has the typical features of cork tissues with a regular and radially aligned structure of suberized cells without intercellular voids, showing a ring structure and a distinction of earlycork and latecork cells. Solid volume fraction was estimated at 25% (22% in earlycork, 36% in latecork). In Q. cerris cork cells are smaller, cell wall thickness and solid volume fraction are higher, and the tissue is less homogeneous with a higher content of ligniﬁed inclusions than in Q. suber cork. These factors will negatively inﬂuence quality in regard to density and mechanical properties associated to elasticity. However, this does not impair its use for production of granulates and agglomerates, e.g. for insulation and energy absorption. Separation of the cork fraction from the bark is a step required before further processing and use.